Comparative politics : explaining democratic systems - Judith Bara; Pennington, Mark (New Delhi Sage Publications, 2023)
This book provides a distinctive new introduction to the study of comparative politics at undergraduate level. Rich in case study material and global in coverage, Comparative Politics sets out the basic theoretical and methodological foundations for studying different political systems as well as the key structures and actors of which they are comprised.Part I explores the nature of comparative methodology and introduces students to the major theoretical paradigms that seek to explain the operation of institutions in democratic states and facilitate comparison across different political systems.Part 2 examines the institutional structures of the modern state, outlining the key features such as the electoral systems and territorial and functional divisions of government across a range of modern states.Part 3 analyses the role of key actors, such as voters and parties, interest groups and social movements, the bureaucracy and the judiciary.This book will be an essential primer for students of comparative government and politics as well as introductory courses in political science concepts and methods.
Keywords: Comparative Politics